'The women are taking over': Exploring hegemonic masculinities in elementary principalship. (January 2021) - MacKinnon, Kenneth
This article explores the experiences of both male and female principals in the Greater Toronto Area (GTA) as they navigate principalship through a gendered lens. Interviews with these principals reveal the presence and impact of hegemonic masculinities on the ability of both male and female principals to lead their schools. These conversations reveal a series of discourses that repeatedly emerged: 'The women are taking over'; 'The "detached" male principal'; 'You're tough, you can handle it, man'; and 'I'd rather work for a man'. One would think that the influx of more female principals in the GTA over the past 10 years would inspire positive changes to the role of principal, a role that was largely created by and for men to inhabit. Sadly, this is not the case as both male and female principals continue to uphold hegemony while at the same time struggle under its effects. This article takes the position that principalship provides the potential to create a space where women and men can find agency, a place of resistance that works against the gendered discourses at play in their daily work lives. Unfortunately, it appears that this space does not yet exist, and this article suggests that recognition of the problem is the first step towards finding such a space.